1987
DOI: 10.1016/s0025-6196(12)65077-0
|View full text |Cite
|
Sign up to set email alerts
|

New Antiarrhythmic Drugs: Tocainide, Mexiletine, Flecainide, Encainide, and Amiodarone

Abstract: Tocainide, mexiletine, flecainide, encainide, and amiodarone are antiarrhythmic agents that have recently been approved by the Food and Drug Administration for general use in the treatment of ventricular arrhythmias. All five agents are effective in the treatment of patients with ventricular arrhythmias, whereas encainide, flecainide, and amiodarone are also useful in patients with supraventricular arrhythmias and the Wolff-Parkinson-White syndrome (although not yet approved for these indications). Tocainide a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

1989
1989
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(14 citation statements)
references
References 139 publications
(176 reference statements)
0
14
0
Order By: Relevance
“…JTc was, if anything, shortened but no other electrophysiological changes were seen. Intravenous (2-3 mgkg-') canine studies (Yoon & Han, 1982;Costard-Jackle & Franz, 1989), intravenous clinical studies (Seipel & Breithardt, 1978;Jewitt, 1978) and clinical oral studies (reviewed by Kreuger et al, 1987;Nestico et al, 1988) have reported little or no effect of mexiletine on intracardiac conduction, refractory periods or repolarization although shortening of the latter has sometimes been observed. Experimental studies using 2 mgkg-' do however suggest that mexiletine may slow ventricular conduction (Bajaj et al, 1987) and prolong the ventricular refractory period (Costard-Jackle & Franz, 1989) but only at cycle lengths substantially shorter than those used in our study whilst at long cycle lengths, prominent short- In contrast to Org 7797, disopyramide (2mgkg-1) in antiarrhythmic doses (Marshall & Parratt, 1979;Hashimoto et al, 1982) increased JTc (by 6%) and QT during pacing (by 16%) indicating a clear prolongation of ventricular repolarization.…”
Section: Discussionmentioning
confidence: 99%
“…JTc was, if anything, shortened but no other electrophysiological changes were seen. Intravenous (2-3 mgkg-') canine studies (Yoon & Han, 1982;Costard-Jackle & Franz, 1989), intravenous clinical studies (Seipel & Breithardt, 1978;Jewitt, 1978) and clinical oral studies (reviewed by Kreuger et al, 1987;Nestico et al, 1988) have reported little or no effect of mexiletine on intracardiac conduction, refractory periods or repolarization although shortening of the latter has sometimes been observed. Experimental studies using 2 mgkg-' do however suggest that mexiletine may slow ventricular conduction (Bajaj et al, 1987) and prolong the ventricular refractory period (Costard-Jackle & Franz, 1989) but only at cycle lengths substantially shorter than those used in our study whilst at long cycle lengths, prominent short- In contrast to Org 7797, disopyramide (2mgkg-1) in antiarrhythmic doses (Marshall & Parratt, 1979;Hashimoto et al, 1982) increased JTc (by 6%) and QT during pacing (by 16%) indicating a clear prolongation of ventricular repolarization.…”
Section: Discussionmentioning
confidence: 99%
“…We found an age-related decline in the oral clearance (CL/F) of flecainide acetate [5], which is a CYP2D6 substrate and a strong sodium channel blocker commonly used to treat various supraventricular tachyarrhythmias [6][7][8]. Flecainide undergoes renal excretion and hepatic metabolism by its conversion to m-O-dealkylated flecainide (MODF) and subsequent oxidation to m-O-dealkylated lactam [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Flecainide acetate, a Vaughan–Williams class Ic anti‐dysrhythmic agent, is commonly used as a strong sodium channel blocker for a variety of supraventricular tachydysrhythmias (1, 2) that cannot be controlled by other anti‐dysrhythmic agents or by catheter ablation. Therapeutic levels of serum flecainide are currently reported to be 300–1000 ng/mL for supraventricular tachydysrhythmias, including atrial fibrillation (AF) (3).…”
Section: Introductionmentioning
confidence: 99%